CONCEPTION OF NATIONALITY IN INTERNATIONAL AND HOME REGISTRATION SYSTEM - T. V. Erina (Russian Journal of Economics and Law)
The author considers principles of rationality, ways of its realization and variants of its usage that can lead to improvement of registration and making decisions.